ANALISIS PERILAKU MASYARAKAT DALAM MEMILIH MEREK HANDPHONE DENGAN MENGGUNAKAN ANALISIS FAKTOR (Studi Kasus Mahasiswa Universitas Udayana) - RANTASARI, SANG AYU PUTRI INDRIA; SUCIPTAWATI, NI LUH PUTU; TASTRAWATI, NI KETUT TARI (E-Jurnal Matematika, 2015)
The purpose of this study is to determine factors that influence consumer’s decisions to choose a brand of mobile phone and to determine the dominant factor influencing consumer’s decision in choosing brand of mobile phone . The method used is factor analysis . Factor analysis is one part of the analysis of several variables that are used to reduce the data , which is a process to summarize a number of independent variables associated with the factors named mapped or grouped into a new variable . The results showed that there are seven factors that influence consumers to choose the brand of mobile phone: the quality factor, brand, features, product durability, shape or model, price, and warranty. While among the seven factors, the quality factor is a dominant factors that affect consumers to choose brand of mobile phone .
Keywords: Brand of Mobile Phone; Udayana University Student; Factor Analysis